Access to water and drinking water supply coverage: Understanding water security in Kerala - P. Maneesh (Indian Journal of Economics and Development, 2015)
Background/Objectives: Water scarcity is the main problems that the world faces today. This study made an enquiry about the accessibility and coverage of drinking water and explores the water security aspect of kerala. Methods/Statistical analysis: The study is based on secondary data. The data were collected from the website of kerala state planning board, department of water supply and sanitation, and Registrar General and Census Commissioner of India. Data are also been collected from other sources such as: journals, newspapers, magazines, thesis and electronic resources. Findings: The state with a lot of rivers and lakes is converted to the drought prone area due to the wreck less sand mining and quarrying mushrooming over the years. As a result, Kerala has witnessed a decline in percapita water availability over the years. The availability of rain, surface and ground water exhibit a declining trend. All the habitations in kerala have achieved water availability of above 40 Litre Per Capita per Day. Access to improved water supply exists, that is at least 40 Litres/capita/day of safe drinking water are provided within a distance of 500 m or 1km of elevation difference. Therefore water scarcity is not a severe problem in kerala, but the declining the quantity of water indicating the forthcoming water crisis. Improvements/Applications: An integrated institutional system for groundwater conservation and recharging measures needs to be promoted to conserve the major source of drinking water.